Practical bomb scene investigation - Thurman, James T. (CRC series in practical aspects of criminal and forensic investigations, 2017)
Now in its Third Edition, Practical Bomb Scene Investigation explores the investigative process that improvised explosive device (IED) specialists undertake at the scene of an explosion. Providing easy-to-understand, step-by-step procedures for managing and processing a bomb scene, it enables investigators to find the evidence and then make sense of what is found. The book is not only a roadmap on how to find and collect evidence and assess the scene, but also provides instruction on identifying the bombmaker's signature through latent print, DNA, explosive residue, metallurgical, and toolmark examination and forensic analysis.